(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Soil physico-chemical properties are an important phenomenon for sustainable crop production and maintenance of optimum soil health. Hence, a laboratory measurement was conducted with soil samples of three years long experimental field of the Department of Soil Science, Bangladesh Agricultural University, Mymensingh to assess the changes in five selected soil physico-chemical properties viz. soil texture, bulk density, soil pH, total nitrogen and organic matter. The experiment was laid out in a split plot design with two water regimes (continuous flooding and alternate wetting & drying) in the main plots and five fertilizer treatments (N0 - control, N1- 140 kg N/ha as PU, N2- 104 kg N/ha as USG (2× 1.8 g/ 4 hills), N3 - 5 t CD + PU @ 140 kg N /ha on IPNS basis and N4- 5 t CD + USG (2× 1.8 g/ 4 hills @ 104 kg N/ha)) in the subplots under rice-rice cropping pattern with three replications. After three years, soil samples were collected at 0-5 and 5-10 cm soil depths for measuring bulk density and at 0-10 cm depth for other soil properties and analyzed. Results found that % sand, % silt, % clay, bulk density and soil pH was not changed significantly compared to initial status. Percentage of total nitrogen and organic matter was significantly affected by irrigation and fertilization. Total nitrogen (%) was higher in AWD whereas organic matter (%) was higher in CF practice. The highest total nitrogen (%) and organic matter (%) was found in N4 treatment in which USG was applied in combination with cowdung as organic manure. It can be suggested that N4 treatment was formed good combination for sustaining chemical properties of soil. Further long- term experimentation will be needed to know the changes in soil properties for sustainable crop production and improving soil health. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (2), 65-71